Education-Migration Nexus: Understanding Youth Migration in Southern Ethiopia - Tesfaye Semela; Logan Cochrane (MDPI AG, 2019)
The purpose of this study is to unravel the education–migration nexus in the African context, specifically Ethiopia. It examines why young people terminate their education to migrate out of the country. The study applies de Haas’ aspiration—capability framework and Turner’s macro, meso and micro sociology as its analytical lenses. It offers unique insight into the terrain of youth migration in southern Ethiopia based on empirical data obtained from two rural sub-districts known for high levels of youth out-migration. Data are generated based on interviews with would-be migrant youth, parents, teachers and school principals. The findings reveal that education has both direct and indirect impacts on youth migration. On the other hand, the results indicate that though terminating school could have negative ramifications on human capital accumulation at micro and macro levels, migration can positively impact households and local communities through investments made by individual migrants, migrant-returnees, and remittance-receiving households in small businesses or community development projects, which included better resourced schools.